Medical acupuncture in pregnancy: a textbook - Römer, Ansgar (Thieme, 2005)
More and more health care professionals in obstetrics and gynecology are turning to complementary medicine to enhance their patients' comfort and wellness. _x000D__x000D_With …
Includes bibliographical references and index
Keywords: Electronic books; Akupunktur; Geburtshilfe; Schwangerschaft